A c-REL drives atherosclerosis at sites of disturbed blood flow. (4th June 2021) - Ayllón, Blanca Tardajos; Souilhol, Celine; Oakley, Fiona; Evans, Paul C
Abstract : Atherosclerosis is an inflammatory disease that develops preferentially at bends and branches of the vasculature exposed to disturbed flow and low shear stress (LSS). These mechanical conditions modify endothelial cell (EC) physiology by regulating proliferation, inflammation and other fundamental processes. Shear stress alters multiple transcriptional programs, including those regulated by the NF-κB family of transcription factors. Although some members of the NF-κB pathway are known to respond to shear, the influence of this haemodynamic force on the c-Rel NF-κB subunit and its role in atherogenesis are still unknown. The expression and function of c-Rel was studied using human umbilical vein EC (HUVEC) and human coronary artery EC (HCAEC) exposed to LSS or high shear stress (HSS) using in vitro flow systems. Western blotting revealed that LSS strongly induced c-Rel expression in HUVEC and HCAEC. Gene silencing coupled to transcriptome profiling demonstrated that c-Rel promotes pathogenic EC processes (inflammation, proliferation) via induction of p38 MAP kinase and non-canonical p100/p52 NF-κB signalling. Consistently, immunofluorescent en face staining of murine aortas revealed a striking enrichment of c-Rel at LSS regions compared to HSS regions. Genetic deletion of c-Rel, either specifically in EC or in the whole body, rescued EC function, reduced arterial inflammation and decreased atherosclerotic lesion area in hypercholesterolemic AAV-PCSK9-treated mice, indicating that c-Rel promotes atherosclerosis by inducing EC pathological changes. Our data demonstrate that c-Rel promotes EC pathophysiological changes at LSS regions and is a driver of atherosclerosis via activation of MAPK and non-canonical NF-κB pathways. These data identify c-Rel as a novel therapeutic target to reduce atherosclerosis.